Spatial Distribution of Potential Pollution Load Point Source of Bedadung River in the Urban Area Segment - Elida Novita; Ahmad Zaidan Karomi; Hendra Andiananta Pradana (Universitas Muhammadiyah Surakarta, 2022)
The variety of community activities in urban areas and a poor domestic sewage system are thought to affect the water quality of the Bedadung River. The high level of river pollution is caused by the high amount of polluting waste that enters, thus increasing the pollution load. Point source pollutant sources are sources of pollutants originating from certain sources that can be identified directly, such as domestic waste disposal, industrial activities, and others. Organic pollutants from domestic waste that enter the river can reduce the dissolved oxygen concentration in the river which can affect the quality of river water. The quality of water from pollutants can be indicated by knowing the concentration of the oxygen content in the water. To find out, it is necessary to measure the amount of BOD (Biochemical Oxygen Demand). The BOD value can be used as an index number to measure the level of pollutants from waste in a water system. In addition, changes in land use are also the impact of population growth and increased human activity. Land-use changes that ignore the principles of ecosystem sustainability tend to harm the environment, including a decrease in water quality. This study was conducted to determine the potential point source pollution load of Bedadung River in the Urban Area using information about the Bedadung River both spatial data and pollutant water quality (BOD) data. All data is combined and processed using Geographical Information Systems (GIS) technology. The data were analyzed and plotted into a map depicting the distribution of potential point source pollutant loads in the Bedadung River Urban Area Segment. The results of the analysis of land cover pollutant source areas based on the boundary include rice fields of 18.97%, fields of 5.98%, gardens of 12.85%, rivers of 12.25%, and settlements having the largest land area of 49.96% of the total area of the study area. The results of the calculation of the potential point source pollution load showed that the highest potential pollution load value was in the Kaliwates village of 13.966 kg/day, the lowest was in the Antirogo village of 0.004 kg/day and the total point source pollution load was 36.31 kg/day.